2015
DOI: 10.1111/den.12431
|View full text |Cite
|
Sign up to set email alerts
|

Cold snare polypectomy: Does snare type influence outcomes?

Abstract: Snare type appears to be an important determinant of completeness of excision when removing small polyps by the cold snare technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(87 citation statements)
references
References 38 publications
(47 reference statements)
4
80
2
Order By: Relevance
“…Our study confirmed and concurs with previous studies that CSP is a very safe procedure and a justifiable choice of procedure in colorectal . The postoperative hemorrhage rate was 0.1% even though 52 patients (15.2%) were receiving various antithrombotic treatments.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study confirmed and concurs with previous studies that CSP is a very safe procedure and a justifiable choice of procedure in colorectal . The postoperative hemorrhage rate was 0.1% even though 52 patients (15.2%) were receiving various antithrombotic treatments.…”
Section: Discussionsupporting
confidence: 92%
“…Our study also showed that the histopathological margins of resected specimens using CSP were negative in 70.5% of lesions. Previous studies have also reported low rates of a negative histopathological margin (50–60%) . Compared to other endoscopic therapies, this rate was lower than that of EMR for tumors <20 mm in diameter (78.3%, 489/624) in our previous study .…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…An association between the types of snare used and complete resection rates of polyps has been reported . For example, we showed that cold dedicated snares were superior to traditional snares for removal of 8–10‐mm non‐pedunculated polyps and pedunculated polyps ≤10 mm .…”
Section: Devices For Cold Snare Polypectomymentioning
confidence: 60%